Gender-Based Violence in Children's Sport - Kerr, Gretchen (Women, Sport and Physical Activity, 2023)
This book addresses the major forms of Gender-Based Violence (GBV) in children's sport, including sexual, physical, and psychological violence and neglect. It reviews the historical, sociocultural, and political influences on violence towards children, and sets out future agendas for research and practice to eliminate GBV in sport. The book argues that for GBV to occur and be sustained over time, it must be facilitated by a system that enables this violence, protects the perpetrator, disables bystanders, silences the victims, and/or fails to provide a structure by which to address victims' or bystanders' concerns. Drawing on empirical research from across a range of disciplines, including sport sociology, sport psychology, developmental psychology, and coaching, and examining real life case studies of GBV in sport at all levels, the book makes a powerful case for radical change in our current systems of sport governance, safeguarding, and athlete welfare. This is important reading for any student, researcher, policy-maker, coach, welfare officer or counsellor with an interest in sport, gender studies, safeguarding, criminology, or sociology.